The Effect of Knowledge Sharing Practices on Organization Performance - Al Ali, Adel Hasan (2013)
Knowledge sharing is considered as one of the most critical steps in the Knowledge Management process. Likewise, knowledge sharing practices is also disputed to have a positive effect and able to improve the performance of an organization. It is always good to share the good and bad experiences among the team members in any organization as this would allow others to either try to use the way of doing business better or also to avoid the negative decisions that others have gone through. This study examines the concept of knowledge, the factors that negatively or positively help the facilitation of knowledge sharing, and the effects or impact of knowledge sharing on the organizational performance of an investment company in the UAE. Knowledge sharing practices are hypothesized to have a positive effect on five areas in an organization: the human capital or employee competencies, employee’s productivity, employee’s quality of work and performance, the effectiveness of the organization, and the customer satisfaction. It is hypothesized that positive effect on these areas will have a positive effect on the performance of an organization. For each emphasis area, this study discusses the conceptual framework used and recapitulates the empirical research results. This research found out that knowledge sharing practices improves the areas mentioned above and this will lead to an improvement in the performance of the organization. The paper concludes with the recommendations such as establishment of knowledge repository and constant meeting across the teams to better improve the knowledge sharing practices in AAA Real Estate Development Company, as well as future research to better capture the knowledge in an organization.